2016
DOI: 10.1007/s10517-016-3575-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Biochemical Markers of Endothelial Dysfunction and Organ Damage under Conditions of Experimental Nonferrous Metal Intoxication

Abstract: Chronic nickel intoxication caused by parenteral nickel chloride administration (0.5 mg/kg of body weight) to Wistar rats led to ROS generation inducing LPO in erythrocyte membranes and homogenates of renal, liver, and myocardial tissue. Superoxide dismutase (SOD) activity was inhibited, while catalase activity and ceruloplasmin concentration increased. LPO and its products disrupted nitric oxide production and reduced its bioavailability, which led to the development of endothelial dysfunction and impaired mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Given the alarmingly high prevalence of Ni allergy and obesity in the general population and the hints coming from previous preclinical studies suggesting a possible correlation between Ni and metabolic outcomes[ 4 , 6 , 7 ], our aim has been to investigate this in human subjects. We therefore assessed for symptoms and signs of ACD/SNAS all overweight and obese subjects being admitted to the High Specialization Center for the Care of Obesity, Sapienza University of Rome, from 2010 to 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Given the alarmingly high prevalence of Ni allergy and obesity in the general population and the hints coming from previous preclinical studies suggesting a possible correlation between Ni and metabolic outcomes[ 4 , 6 , 7 ], our aim has been to investigate this in human subjects. We therefore assessed for symptoms and signs of ACD/SNAS all overweight and obese subjects being admitted to the High Specialization Center for the Care of Obesity, Sapienza University of Rome, from 2010 to 2016.…”
Section: Introductionmentioning
confidence: 99%
“…MDA is one of the end products of lipid peroxidation, which is recognized as a sentinel of the cellular oxidation status [36]. In the present study, the levels of MDA enhanced by H 2 O 2 induction were reduced in the AEE—preincubated HUVECs—and the optimal dose of AEE was found to be 1 μ M. The dysfunction of the antioxidant system is responsible for the generation of oxidative stress markers [34]. In the present study, the GSH/GSSG ratio and the activity of SOD and GSH-Px were altered by H 2 O 2 , which was consistent with the previous studies [37, 38].…”
Section: Discussionmentioning
confidence: 51%
“…Our findings confirmed that the incubation of HUVECs with 300 μ M H 2 O 2 for 6 h caused oxidative stress, indicated by the unbalance between antioxidation and oxidation and the dysfunction of mitochondria and lysosome. To evaluate the oxidative stress of cells, many markers have been reported [3436]. MDA is one of the end products of lipid peroxidation, which is recognized as a sentinel of the cellular oxidation status [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our research has established that oxidative stress leads to a violation of the NO-producing function of the endothelium and a decrease in the content of nitric oxide (NO). Nitric oxide is a messenger molecule that participates in many physiological and pathological processes and has both beneficial and destructive effects [13]. It is an endothelial relaxation factor, formed from L-arginine with the participation of the nitric oxide synthase enzyme (NO synthase).…”
Section: Advances In Health Sciences Research Volume 16mentioning
confidence: 99%